The relationship between perceived stress and support with blood pressure in urban Haiti: A cross-sectional analysis. - Lily D Yan; Jessy G Dévieux; Jean Lookens Pierre; Eliezer Dade; Rodney Sufra; Stephano St Preux; Olga Tymejczyk; Denis Nash; Miranda Metz; Myung Hee Lee; Dan W Fitzgerald; Marie Deschamps; et al. (PLOS Global Public Health, 2022)
Haiti is a low-income country whose population lives under repeated and chronic stress from multiple natural disasters, civil unrest, and extreme poverty. Stress has been associated with cardiovascular (CVD) risk factors including hypertension, and the impact of stress on blood pressure may be moderated by support. The distribution of stress, support, and their association with blood pressure has not been well described in low-income countries. We measured stress and support using validated instruments on cross-sectional enrollment data of a population-based cohort of 2,817 adults living in Port-au-Prince, Haiti between March 2019 and April 2021. Stress was measured using the Perceived Stress Scale, while support was measured using the Multidimensional Scale of Perceived Social Support. Continuous scores were categorized into three groups for stress (low (1-5), moderate (6-10), high (11-16), and five groups for support (low (7-21), low-moderate (22-35), moderate (36-49), moderate-high (50-64), high (65-77)). Linear regression models were used to quantify the associations between: 1) support and stress adjusting for age and sex, and 2) stress and blood pressure adjusting for age and sex. A moderation analysis was conducted to assess if support moderated the relationship between stress and blood pressure. The cohort included 59.7% females and the median age was 40 years (IQR 28-55). The majority had an income <1 US dollar per day. The median stress score was moderate (8 out of 16 points, IQR 6-10), and median support score was moderate to high (61 out of 77 points, IQR 49-71). Stress was higher with older ages (60+ years versus 18-29 years: +0.79 points, 95% CI 0.51 to 1.08) and in females (+0.85 points, 95% CI +0.65 to +1.06). Support was higher in males (+3.29 points, 95% CI 2.19 to 4.39). Support was inversely associated with stress, adjusting for age and sex (-0.04 points per one unit increase in support, 95% CI -0.04 to -0.03). Stress was not associated with systolic or diastolic blood pressure after adjustment for age and sex. Support did not moderate the association between stress and blood pressure. In this urban cohort of Haitian adults living with chronic civil instability and extreme poverty, perceived levels of stress and social support were moderate and high, respectively. Contrary to prior literature, we did not find an association between stress and blood pressure. While support was associated with lower stress, it did not moderate the relationship between stress and blood pressure. Participants reported high levels of support, which may be an underutilized resource in reducing stress, potentially impacting health behaviors and outcomes.